Vedde Ash constrains Younger Dryas glacier re-advance and rapid glacio-isostatic rebound on Svalbard - Farnsworth, Wesley Randall; Ingólfsson, Ólafur; Mannerfelt, Erik S.; Kalliokoski, Maarit H.; Gudmundsdottir, Esther Ruth; Retelle, Michael; Allaart, Lis; Brynjólfsson, Skafti; Furze, Mark; Hancock, Holt John; Kjær, Kurt H.; Pieńkowski, Anna J.; et al. (Quaternary Science Advances, 2021)
The distal deposition of tephra from explosive volcanism has the potential to geochronologically constrain sedimentary archives and landforms. With this technique, we constrain a Late Glacial glacier re-advance on Svalbard and suggest that glacioisostatic emergence rates during the Younger Dryas chronozone were at least three times greater than previous estimates. The identification of cryptotephra (i.e., non-visible) horizons, outside the extent of visible fallout, has greatly expanded the field of application of tephrochronology. While the cryptotephra revolution has triggered a burst of investigations using low-concentration tephra to constrain distal sedimentary sequences, as of yet, few investigations have used this tool to constrain the age of glacial landforms. Here we constrain a moraine formed during a glacier re-advance (12.8–12.2 cal ka BP) into a high relative sea level during the early Younger Dryas chronozone, with the first identified occurrence of the Icelandic Vedde Ash on Svalbard. Low concentrations (∼63 shards/g dried sediment) of the bimodal Vedde Ash (rhyolitic long axis c. 30–90 μm; basaltic c. 35–100 μm) were identified in a lake sediment sequence collected from the Heftyebreen glacier foreland, in a tributary valley to Grønfjorden, western Spitsbergen. Given that the cryptotephra was deposited within a lacustrine isolation basin, we further reconstruct a minimum rate of glacio-isostatic emergence during the end of the Late Glacial. Strong and longstanding evidence suggests Svalbard's west-coast cirque glaciers were less extensive during the Late Glacial than the Late Holocene. However, the Late Glacial Heftyebreen moraine suggests Svalbard glacier dynamics during this period may have been more complex.